Apakah Capital Intensity Meningkatkan Agresivitas Pajak? - Tahlila, Siti Najwa Dena; Tjaraka, Heru; Rahmiati, Alfa (Magister Akuntansi Universitas Pancasila, 2024)
This study aims to analyze the effect of capital intensity on tax aggressiveness by using control variables consisting of size, leverage and profitability. The sample is the financial reports of companies in the chemical manufacturing sector listed on the IDX in 2017-2021 using the purposive sampling technique method, obtained 22 chemical companies with 110 observational data for 5 years from 2017-2021. Data collection techniques used are documentation and literature study. Data were analyzed using descriptive statistics and simple linear regression analysis. The results showed that by model fit test (F test) capital intensity and control variables consisting of leverage, size and profitability have an influence on tax aggressiveness. Meanwhile, partially, capital intensity has a negative and significant effect on tax aggressiveness. It can be concluded that the higher the value of capital intensity, the lower the tax aggressiveness. The contribution of this research is as information for companies to be able to take advantage of fiscal as a way to minimize tax costs and is a legal tax planning.